PENGARUH PELATIHAN DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR SEKRETARIAT DPRD KABUPATEN MAJENE - Lina Mariana; Sri Indira Hartawati (Journal of Social Sustainability Management, 2022)
This study aims to determine the effect of training on employee performance at the Majene Regency DPRD Secretariat office, to determine the effect of job satisfaction on the Majene Regency DPRD Secretariat office and to determine which variable has a more dominant influence on the Majene Regency DPRD Secretariat office. This type of research is quantitative with data analysis technique using SPSS. The population in the study amounted to 45 people and the sample was drawn using the census method (all populations were samples). The results showed that: 1) Training had an effect on employee performance at the Majene Regency DPRD Secretariat Office; 2) Job satisfaction has an effect on employee performance at the Majene Regency DPRD Secretariat Office; 3) Of the two variables above, Training and Job Satisfaction, the variable Job Satisfaction has more influence on Employee Performance